(untitled) (Research, Society and Development, 2021)
Nowadays, people are increasingly trying to fit a standard of beauty and the search for the perfect smile can bring harm and frustration to the patient, if the professional does not follow the necessary criteria to perform aesthetic interventions, as in the case of resin veneers composed. The objective of this work is to describe a clinical case where the replacement of composite resin veneers in the upper anterior dental elements by new resin veneers was performed in search of esthetic and anatomical adequacy and to discuss about this treatment. The patient sought care at the dental office complaining about his old facets, where he found the color unpleasant, also stating that when he performed his oral hygiene there was bleeding. In view of such patient situations and clinical analysis, immediate tooth whitening of the lower arch was proposed, as well as removal of the 10 pre-existing veneers and a new execution of 10 veneers in resin following the aesthetic and functional principles. In order to perform multiple esthetic restorations, it is essential that the Dental Surgeon is aware of the indications, possible limitations and knowledge of the patient’s dental anatomy, also respecting periodontal tissues and structures. Thus, a properly qualified planning to perform this procedure is essential so that the patient will not have any discomfort, ensuring the success of the treatment.